Integrated View on the Role of Vitamin D Actions on Bone and Growth Plate Homeostasis. (18th November 2021) - Verlinden, Lieve; Carmeliet, Geert
ABSTRACT: 1, 25(OH)2 D3, the biologically active form of vitamin D3, is a major regulator of mineral and bone homeostasis and exerts its actions through binding to the vitamin D receptor (VDR), a ligand‐activated transcription factor that can directly modulate gene expression in vitamin D‐target tissues such as the intestine, kidney, and bone. Inactivating VDR mutations or vitamin D deficiency during development results in rickets, hypocalcemia, secondary hyperparathyroidism, and hypophosphatemia, pointing to the critical role of 1, 25(OH)2 D3 ‐induced signaling in the maintenance of mineral homeostasis and skeletal health. 1, 25(OH)2 D3 is a potent stimulator of VDR‐mediated intestinal calcium absorption, thus increasing the availability of calcium required for proper bone mineralization. However, when intestinal calcium absorption is impaired, renal calcium reabsorption is increased and calcium is mobilized from the bone to preserve normocalcemia. Multiple cell types within bone express the VDR, thereby allowing 1, 25(OH)2 D3 to directly affect bone homeostasis. In this review, we will discuss different transgenic mouse models with either Vdr deletion or overexpression in chondrocytes, osteoblasts, osteocytes, or osteoclasts to delineate the direct effects of 1, 25(OH)2 D3 on bone homeostasis. We will address the bone cell type–specific effects of 1, 25(OH)2 D3 in conditions of a positive calcium balance, where the amount of (re)absorbed calcium equals or exceeds fecal and renal calcium losses, as well as during a negative calcium balance, due to selective Vdr knockdown in the intestine or triggered by a low calcium diet. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.